41 Evaluation of the dose delivered to patients during a bone scan coupled with an examination CT scan and practice optimization. (December 2018) - Sarcy, S.; Maisonobe, J.A.; Jenny, C.; Kas, A.; Soret, M.
Abstract : Introduction: An inventory of the use of CT coupled to SPECT and of CT patient exposure is carried out in our nuclear medicine department for bone scan examinations. Our goal is to optimize our CT scans based on medical needs in this context. Methods: 50 patients who underwent a SPECT/CT bone scan on Discovery NM/CT 670 (GE Healthcare) from January 2017 to March 2018 are included in the study. For these acquisitions, CT parameters are: 2.5 mm slices, pitch of 1.375, rotation time 0.7 s, voltage 120 kV. The current is modulated according to the corpulence in z (AutomA®) and x, y (Smart mA®) with a maximum current (mAsmax ) of 110 mA. The noise index (NI) is set to 26.9. Patient weight, height, activity of 99m Tc administered (8 MBq/kg), anatomical area explored and the Dose Length Product (DLP) are recorded. For each patient, the absorbed dose delivered by the radionuclide, the effective dose delivered by the CT and the total effective dose are calculated. Several CT acquisitions are then performed with CT phantoms, varying the NI, pitch and mAsmax . The image quality of the CT obtained is analyzed in terms of spatial resolution, contrast and noise. Results: For the anatomical area "head and neck (H&N)", "abdomen and pelvis (AP)" and "thorax, abdomen and pelvis (TAP)", mean DLP is 49.5; 157.1 and 260.4 mGy.cm and injected activity is 526; 625 and 573 MBq, respectively. The total effective dose is 3.6; 6.1 and 7.0 mSv. The CT exam contributes to: 3.6%; 36% and 48.9% of the total effective dose, respectively in average. For phantom acquisitions, only the reduction of the NI to 20 and the increase of the mAmax to 140 mA allowed a clear improvement of the image quality. Conclusions: In the context of bone scintigraphy, CT for the H&N areas contributes little to the total dose delivered to the patient. However, its contribution is not negligible for the AP and TAP area. There are no diagnostic reference levels for SPECT/CT bone scan. However, the DLP recorded for the TAP is 2.1 times lower than the guide value proposed by the SFMN for PET/CT TAP (550 mGy.cm). After discussion with the medical team, an improvement in CT contrast in the soft tissues is desirable in an oncological context. For this purpose, we proposed to change the NI to 20 and increase the mAmax to 140 mA. This implies an increase in Computed Tomography Dose Index by a factor of 1.5. It is also proposed to adjust the voltage according to the patient's body mass index. Following the implementation of these recommendations, it will be necessary to assess the dose and image quality indexes again. A similar study is underway for the other SPECT/CT exams performed in the department.